A proof‐of‐concept study: Mirabegron, a new therapy for overactive bladder. Issue 8 (19th February 2013) - Chapple, Christopher R.; Amarenco, Gerard; López Aramburu, Miguel A.; Everaert, Karel; Liehne, Josef; Lucas, Malcolm; Vik, Viktor; Ridder, Arwin; Snijder, Robert; Yamaguchi, Osamu; ,
Abstract Aims To evaluate the potential of mirabegron, a selective β3‐adrenoceptor agonist, for treatment of overactive bladder (OAB) symptoms. Methods A multicenter, randomized, double‐blind, double‐dummy, parallel group, placebo and active‐controlled, Phase 2, proof‐of‐concept study was conducted. Eligible patients (n = 314) were enrolled into a single‐blind, 2‐week placebo run‐in period followed by a randomized, double‐blind, placebo‐controlled treatment period. Patients received mirabegron 100 or 150 mg twice‐daily (BID), placebo or tolterodine 4 mg extended release (ER) once‐daily for 4 weeks. Primary endpoint was change from baseline to end‐of‐treatment in mean number of micturition episodes per 24 hr. Secondary endpoints included changes in mean volume voided per micturition; mean number of urinary incontinence, urgency urinary incontinence, and urgency episodes per 24 hr; severity of urgency; nocturia, and quality of life measures. Safety parameters included adverse events, laboratory tests, electrocardiogram parameters and post‐void residual volume. Results Mirabegron 100 and 150 mg BID resulted in a statistically significant improvement versus placebo in mean change from baseline to end‐of‐treatment in the primary endpoint of micturition frequency (2.2 micturitions/24 hr vs. 1.2 micturitions/24 hr for both doses, adjusted P ≤ 0.01 for both comparisons). Mirabegron had a statistically significant effect versus placebo for most secondary endpoints, including quality of life variables. Despite a small increase in pulse rate, mirabegron demonstrated good safety and tolerability. Conclusions Mirabegron was efficacious and well tolerated in patients with OAB symptoms and heralds the first of a new class of oral pharmacological therapy for OAB for more than 30 years. Neurourol. Urodynam. 32:1116–1122, 2013. © 2013 Wiley Periodicals, Inc.